Beyond Extinction: Prolonged Conditioning and Repeated Threat Exposure Abolish Contextual Renewal of Fear-Potentiated Startle Discrimination but Leave Expectancy Ratings Intact - Leer, Arne; Haesen, Kim; Vervliet, Bram (Frontiers in Psychiatry, 2018)
Extinction treatments decrease fear via repeated exposures to the conditioned stimulus (CS) and are associated with a return of fear. Alternatively, fear can be reduced via reductions in the perceived intensity of the unconditioned stimulus (US), e.g., through repeated exposures to the US. Promisingly, the few available studies show that repeated US-exposures outperform standard extinction. US-exposure treatments can decrease fear via two routes: (1) by weakening the CS-US association (extinction-like mechanism), and/or (2) by weakening the subjective US aversiveness (habituation-like mechanism). The current study further investigated the conditions under which US-exposure treatment may reduce renewal, by adding a group in which CS-US pairings continued following fear acquisition. During acquisition, participants learned that one of two visual stimuli (CS+/CS-) predicted the occurrence of an aversive electrocutaneous stimulus (US). Next, the background context changed and participants received one of three interventions: repeated CS-exposures, (2) repeated US-exposures, or (3) continued CS-US pairings. Following repeated CS-exposures, test presentations of the CSs in the original conditioning context revealed intact CS+/CS- differentiation in the fear-potentiated startle reflex, while the differentiation was abolished in the other two groups. Differential US-expectancy ratings, on the other hand, were intact in all groups. Skin conductance data were inconclusive because standard context renewal following CS-exposures did not occur. Unexpectedly, there was no evidence for a habituation-like process having taken place during US-exposures or continued CS-US pairings. The results provide further evidence that US-exposures outperform the standard extinction treatment, and show that effects are similar when US-exposures are part of CS-US pairings.